(untitled) (Web of Teachers: Inderscience Research, 2024)
The syndrome of mutual aggravation of injuries, which occurs as a result of multiple trauma, leads to a significant increase in the overall severity of the victim’s condition. To determine the time of each stage of CFT treatment, to reduce the number of complications, we have developed and introduced into clinical practice an algorithm for providing care for this injury. The tactics of treating patients with CFT, according to the developed algorithm, has an undoubted advantage over the previously used one - the percentage of inflammatory complications are reduced to a minimum: from 18% to 2%. Such an integrated approach increases the importance of triage of victims in order to achieve a therapeutic effect and economic result.